Applied economic analysis
Applied Economic Analysis is a peer-reviewed journal on global economic issues and the principles of economic analysis, with a particular focus on quantitative studies. AEA is published in association with the Spanish Asociación Libre de Economía (ALdE). ... Quantitative studies grounded on mathematics and statistics methods helping to bring economic theory closer to the real world are particularly appreciated.